Lupus enteritis masquerading as Crohn’s disease - Zhu, Xiu-Li (BMC Gastroenterol, 2019)
BACKGROUND: Systemic lupus erythematosus is an autoimmune disease which can affect multiple organs, resulting in significant mortality and morbidity. Lupus enteritis is one of the rare complications of SLE, defined as vasculitis of the intestinal tract, with supportive biopsy findings and/or image. However, lupus enteritis is seldom confirmed on histology or image and the changes of intestinal mucosa are nonspecific. Crohn’s disease is a chronic inflammatory disorder of the gastrointestinal tract which affects any part of the gastrointestinal tract. The diagnosis of CD is confirmed by clinical evaluation and a combination of endoscopic, histology, radiology, and/or biochemical investigations. CASE PRESENTATION: Here we report a rare case of a 71-years-old Chinese male has been diagnosed with lupus enteritis which similar to CD in the aspects of endoscopic, histology, and radiology. So far, there are no relevant cases reported. CONCLUSIONS: The endoscopic appearance of lupus enteritis is nonspecific, on the basis of our case, the features of lupus enteritis can be described as spacious, clean and no moss ulcers which discontinuous involved all gastrointestinal tract.